2010
DOI: 10.1111/j.1360-0443.2010.03248.x
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association of the obesity predisposing FTO rs9939609 genotype with alcohol consumption and risk for alcohol dependence

Abstract: The FTO AA genotype, independently from its effect on BMI, is associated with measures of ethanol consumption and possibly tobacco smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 47 publications
7
58
0
7
Order By: Relevance
“…This observation therefore suggests that FTO may play an important role in the onset and progression of Parkinson's disease. Consistent with this proposition, FTO malfunction has recently been shown to be associated with reduced brain volume in healthy elderly individuals [118], attention deficit disorders [119], and addiction [120] (Table 1). Interestingly, expression of FTO and the corresponding m 6 A profile in distinct subsets of target RNAs appeared to be synchronously modulated by levels of essential amino acids [66], which possibly links the nutritional stress response to m 6 A modification events.…”
Section: N6 Modification and Human Diseasessupporting
confidence: 64%
“…This observation therefore suggests that FTO may play an important role in the onset and progression of Parkinson's disease. Consistent with this proposition, FTO malfunction has recently been shown to be associated with reduced brain volume in healthy elderly individuals [118], attention deficit disorders [119], and addiction [120] (Table 1). Interestingly, expression of FTO and the corresponding m 6 A profile in distinct subsets of target RNAs appeared to be synchronously modulated by levels of essential amino acids [66], which possibly links the nutritional stress response to m 6 A modification events.…”
Section: N6 Modification and Human Diseasessupporting
confidence: 64%
“…Prior studies have suggested several other phenotypes that may be associated with FTO variants, including pancreatic cancer, Alzheimer's disease, attention deficit hyperactivity disorder, and alcoholism (Keller et al, 2011; Lurie et al, 2011; Sobczyk-Kopciol et al, 2011; arcOGEN Consortium et al, 2012; Corella et al, 2012; Reitz et al, 2012; Velders et al, 2012). We did not find evidence for these associations in our data set ( p > 0.05) (Table 4), but in these cases we may be underpowered to find an association, with case sizes of 76 (attention deficit hyperactivity disorder), 183 (pancreatic cancer), 192 (Alzheimer's disease), and 267 (alcoholism) in our population.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence of other putative disease associations with FTO variants that have not achieved genome-wide significance, such as pancreatic cancer, Alzheimer's disease, attention deficit hyperactivity disorder, alcoholism, and osteoarthritis (Keller et al, 2011; Lurie et al, 2011; Sobczyk-Kopciol et al, 2011; arcOGEN Consortium et al, 2012; Corella et al, 2012; Reitz et al, 2012; Velders et al, 2012). These varied disease-SNP associations suggest that SNPs in FTO may have pleiotropic effects.…”
Section: Introductionmentioning
confidence: 99%
“…For example, certain FTO variants account for adverse phenotypes, such as predisposition to obesity [9][10][11][12] and reduced brain volume, 30 while the same allele protects against depression 153 and the risk for alcohol dependence. 154 It is therefore difficult to decide whether a specific allele is problematic or not. This Janus faced character of certain alleles may explain their high prevalence in the population.…”
Section: Discussionmentioning
confidence: 99%